Sistem Monitoring dan Penilaian Kinerja Pegawai Politeknik Penerbangan Medan - Cahyadi, Catra Indra; Nur, Fauziah; Pasa, Inda Tri; Anwar, Syairi; Sukarwoto (Journal of Students‘ Research in Computer Science, 2024)
With the development of the times and the complexity of business demands, organizations need an effective way to measure, manage, and improve employee productivity and performance contributions. The purpose of this study is to monitor and assess employee performance at the Medan Aviation Polytechnic. This research method is quantitative with Software Development Life Cycle with waterfall technique. with sample user admin, pedulitaruna. The results of the study showed that users of 108 employees, the percentage results based on satisfaction with the use of the performance management information system were 9% of employees very satisfied with the use of the performance management information system, 69% of employees satisfied with the use of the performance management information system, 17% of employees neutral in the use of the performance management information system, and 5% of employees dissatisfied with the use of the performance management information system.